2016
DOI: 10.1016/j.jbiomech.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical profile of cancer stem-like cells derived from MHCC97H cell lines

Abstract: Biomechanical properties and cytoskeletal organization of cancer cells are known to be closely related with their aggressive phenotype. In this study, based on atomic force microscopy (AFM), we aimed to evaluate the mechanical property of liver cancer stem-like cells (LCSCs) and compare it with human hepatoma cells (HHCs). LCSCs were enriched from human hepatoma cell line MHCC97H through a sphere culture system. AFM nanoindentation was investigated as a method for measuring the cell stiffness, and reflecting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Further, exogenous alteration of cell stiffness also resulted in changes in metastatic potential of these cells with less stiff cells showing greater invasion and migration (Chen, Allen et al 2019). The results observed in this study corroborated well with earlier studies showing that cancer cells with greater deformability, lower adhesion strength and lower contractile force show enhanced metastatic potential (Swaminathan, Mythreye et al 2011, Kraning-Rush, Califano et al 2012, Byun, Son et al 2013, Sun, Luo et al 2016, Bongiorno, Gura et al 2018). Therefore, with increasingly detailed characterization of biomechanical properties of various subpopulations of cancer cells and ECM, a 'mechanosome' or 'matrisome' signature may be helpful in identifying and isolating the most aggressive cancer cell subpopulations (Roy Choudhury, Gupta et al 2019).…”
Section: Biophysical Characterization Of Cscs and Their Subsetssupporting
confidence: 90%
“…Further, exogenous alteration of cell stiffness also resulted in changes in metastatic potential of these cells with less stiff cells showing greater invasion and migration (Chen, Allen et al 2019). The results observed in this study corroborated well with earlier studies showing that cancer cells with greater deformability, lower adhesion strength and lower contractile force show enhanced metastatic potential (Swaminathan, Mythreye et al 2011, Kraning-Rush, Califano et al 2012, Byun, Son et al 2013, Sun, Luo et al 2016, Bongiorno, Gura et al 2018). Therefore, with increasingly detailed characterization of biomechanical properties of various subpopulations of cancer cells and ECM, a 'mechanosome' or 'matrisome' signature may be helpful in identifying and isolating the most aggressive cancer cell subpopulations (Roy Choudhury, Gupta et al 2019).…”
Section: Biophysical Characterization Of Cscs and Their Subsetssupporting
confidence: 90%
“…Mechanical stimuli and stress has been shown to affect cell behavior in healthy and pathological conditions 2 . Especially in the process of metastasis and cancer stemness, physical factors of interstitial fluid pressure and matrix stiffness play a major role 3, 4 . Information about the effect of physical factors to cells on a three-dimensional (3D) scale is minimal, and that regarding the influence of gravity on the disease condition is negligible.…”
Section: Introductionmentioning
confidence: 99%
“…AFM revealed that the average Young's modulus value for H1299-sdCSCs was 1.52 kPa, which was 0.68-fold lower than that for the parental H1299 at 2.24 kPa. A previous investigation using AFM reported a 0.7-fold lower stiffness in a human hepatoma stem cell line, MHCC97H, compared with that of the parental cells 26 . Other researchers using a microfluidic device reported a higher deformability in ALDH + CSCs isolated from an inflammatory breast cancer cell line, SUM149, than that in ALDH − cells 27 .…”
Section: Discussionmentioning
confidence: 84%